مسوّغات التأسيس وطبيعة الدور لعلم الكلام الجديد: قراءة في أعمال أهمّ منظّريه: Justifications for the Establishment and the Nature of the Role of the New ‘Ilm al-Kalām - Fahmi, Ahmad Lukman; Sebti, Mohammad (UIN Sunan Kalijaga Yogyakarta, 2024)
‘Ilm al-Kalām occupies a central position in the landscape of Islamic thought, as it is considered a practical application of its method of reasoning. Its stagnation can significantly impact other closely related branches of science, potentially leading to the decline and eventual obsolescence of its role, transforming it into a historical rather than an active field of study. This study aims to explore the views of some contemporary thinkers regarding the deficiencies of classical Kalām in addressing the demands of the modern era, and to examine the legitimacy of renewing this discipline, the rationale behind its establishment, as well as the aspects of its evolution and the nature of its new role. The research employs descriptive, analytical, and historical methodologies, gathering data and information from the works of Mutakallimūn and relevant thinkers. The study’s primary conclusion is that ‘Ilm al-Kalām is in crisis due to methodological deficiencies and issues, causing it to lose its relevance in meeting contemporary demands. Therefore, a comprehensive renewal of its entire system of knowledge is necessary, incorporating modern humanities disciplines such as hermeneutics, semiotics, anthropology, sociology, and others. لعلم الكلام مكانة ومركزية ضمن خارطة الفكر الإسلامي، إذ أنه يعد تطبيقا عمليا لمنهج تفكيره، كما أن جموده قد يؤثر على بقية فروع المعرفة المتقاربة معه في الاستمداد، ما قد يؤدى إلى انحسار هذا العلم وموت دوره، فيتحول إلى معرفة تاريخية بدل أن كان معرفة فاعلة. ويهدف هذا البحث إلى مناقشة ما يعتقده بعض المفكرين المعاصرين من قصور علم الكلام الكلاسيكي في مواجهة متطلبات العصر، والوقوف على مدى مشروعية تجديد هذا العلم ومسوغات تأسيسه وجوانب تطويره وطبيعة دوره الجديدة. يعتمد هذا البحث على منهج البحث الوصفي التحليلي والتاريخي، حيث يستند في جمع البيانات والمعلومات إلى كتب المتكلمين والمفكرين المتعلقة بالموضوع. وقد توصل هذا البحث إلى نتائج رئيسية أهمها أن علم الكلام يعاني من أزمات لما فيه من قصور ومشاكل منهجية معرفية، وبالتالي فقد فقد أهميته ومغزاه في الوفاء بمتطلبات العصر، ولهذا السبب فمن الضروري تجديده ليس في جانب من جوانبه المحددة فقط، بل في هندسته المعرفية بأكملها، وضرورة توظيف معطيات العلوم الإنسانية الحديثة مثل الهرمنيوطيقا والسيميائية والانثروبولوجيا وعلم الاجتماع وغيره